2018
DOI: 10.1186/s13104-018-3930-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of needle-stick and sharp object injuries and its associated factors among staff nurses in Dessie referral hospital Amhara region, Ethiopia, 2018

Abstract: ObjectiveThe aim of this study was to assess the prevalence of needle-stick and sharp object injuries among staff nurses in Dessie referral hospital, Amhara region, Ethiopia, 2018.ResultsAmong the 151 study participants, 98 (65%) respondents were males. Seventy-five (48.1%) participants had 4–10 years of experience. The overall prevalence of needle stick and sharp object injury among staff nurses in Dessie referral hospital was 43%. In this study, nurses who worked in the emergency department were 11× more lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 18 publications
1
17
2
3
Order By: Relevance
“…It has been estimated that 600,000 to 800,000 NSIs occur each year, with about half of these injuries not being reported [1]. High rates of NSIs have been reported ranging from 14.9% to 69.4% [2] worldwide including North America [3], eastern European countries [4], western European countries and Russia [5], Saudi Arabia [6], and various Asian countries (India, Singapore, Taiwan, Korea, and China) [7]. NSIs have significant adverse impacts on physical and psychological health as well as productivity loss [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that 600,000 to 800,000 NSIs occur each year, with about half of these injuries not being reported [1]. High rates of NSIs have been reported ranging from 14.9% to 69.4% [2] worldwide including North America [3], eastern European countries [4], western European countries and Russia [5], Saudi Arabia [6], and various Asian countries (India, Singapore, Taiwan, Korea, and China) [7]. NSIs have significant adverse impacts on physical and psychological health as well as productivity loss [8].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that two-handed recapping, which is a common practice among HCWs, is the most common cause of NSIs [21,22]. Dilie et al showed that HCWs who recap needles were 21.3 times more likely to experience NSI [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the excessive working hours, understaffing, and poor care environments, inadequate practices of needle disposal (e.g., recapping) and underspend of essential material (sharps containers) are considered modifiable factors (Cooke & Stephens, 2017). Nonetheless, there is evidence that specific training reduces this risk exponentially (Abebe, Kassaw, & Shewangashaw, 2018). Overall, different observed practices potentiate the risk of PIVC-related contamination, contradicting the need for aseptic technique adherence during all aspects of PIVC management.…”
Section: Discussionmentioning
confidence: 99%